2021
DOI: 10.1149/2162-8777/abe094
|View full text |Cite
|
Sign up to set email alerts
|

(3-Aminopropyl)trimethoxysilane Self-Assembled Monolayer as Barrier of Porous SiOCH for Electroless Cu Metallization: Optimizations of SiOCH Hydroxylation and Monolayer Functionalization

Abstract: Self-assembled monolayers (SAMs) are potential diffusion barriers of nanoporous carbon-doped organosilica (p-SiOCH) for Cu metallization. A concern regarding silanization of the p-SiOCH using a wet chemical process is that its dielectric properties and bonding structures could be damaged by the chemical solution used, which is rarely addressed. In this study, the capacity of various (3-aminopropyl)trimethoxysilane self-assembled monolayers (APTMS-SAMs) as a barrier of p-SiOCH for electroless Cu metallization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The patterned SiO 2 /Si substrate was then subjected to a succession of wet chemical treatments, as detailed elsewhere before, 12,19 from sonication clean, hydroxylation, APTMS silanization, functionalization, Ni seeding, finally to Cu electroless deposition, as schematically shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The patterned SiO 2 /Si substrate was then subjected to a succession of wet chemical treatments, as detailed elsewhere before, 12,19 from sonication clean, hydroxylation, APTMS silanization, functionalization, Ni seeding, finally to Cu electroless deposition, as schematically shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, our previous studies have shown that the APTMS-SAM synthesized here was about 1.5 nm thick and is terminated by highly oriented −NH 2 groups. 12,18,19 After the silanization, the sample was ultrasonically cleaned by anhydrous toluene for 5 min, followed by 5 min of deionized water rinsing three times to remove the APTMS residues. Finally, the sample was heated at 100 °C for 15 min to remove residual toluene and water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations